Definición de religión y organización con fines religiosos en el ordenamiento jurídico estadounidense - Celador Angón, Óscar (Ius canonicum, 2021)
The purpose of this research is to analyse the definition of religion and religious organization in the U.S. legal system, as well as the relationship - or lack of a relationship - between such a definition and the principles that shape the U.S. constitutional model: the religious neutrality of public powers, and the separation between the State and religious organizations. To this end, the paper explores the decisions of the federal Supreme Court in contexts where it was necessary to determine the meanings of religion and religious organizations.